2019
DOI: 10.1200/jco.18.02052
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Metastatic Relapse and Monitoring of Therapeutic Efficacy by Ultra-Deep Sequencing of Plasma Cell-Free DNA in Patients With Urothelial Bladder Carcinoma

Abstract: PURPOSE Novel sensitive methods for early detection of relapse and for monitoring therapeutic efficacy may have a huge impact on risk stratification, treatment, and ultimately outcome for patients with bladder cancer. We addressed the prognostic and predictive impact of ultra-deep sequencing of cell-free DNA in patients before and after cystectomy and during chemotherapy. PATIENTS AND METHODS We included 68 patients with localized advanced bladder cancer. Patient-specific somatic mutations, identified by whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
272
2
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 357 publications
(333 citation statements)
references
References 32 publications
14
272
2
8
Order By: Relevance
“…Christensen et al [46] presented promising results. They analyzed longitudinal cfDNA samples of 68 patients with localized MIBC before NAC, after NAC, and after RC.…”
Section: Next-generation Sequencingmentioning
confidence: 97%
“…Christensen et al [46] presented promising results. They analyzed longitudinal cfDNA samples of 68 patients with localized MIBC before NAC, after NAC, and after RC.…”
Section: Next-generation Sequencingmentioning
confidence: 97%
“…Comprehensive cancer panels, as well as whole genome and exome sequencing, can also be used to interrogate somatic copy number alterations (SCNAs) from plasma DNA, with varying resolution depending on the sequence modality and depth [18,19]. Personalized, bespoke sequencing assays have shown sensitivity for the detection of urothelial and colorectal cancers [20,21]. The success of these approaches has been thought to depend upon high tumor burden and the propensity of the tumor to shed circulating tumor DNA (ctDNA) into the bloodstream with proportional contribution of subclones to the ctDNA pool [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed ultra-deep sequencing (median 10500-fold coverage depth) of plasma detected tumor-identical mutations in localized advanced BC. 30 To detect low VAF mutations in plasma cfDNA, high-coverage depth data would be need. Our data suggested that high VAF mutant could be detected in urine of urothelial BC, but not in plasma.…”
Section: Discussionmentioning
confidence: 99%